Information Technologies as the Main Component of Formation of Professional and Communicative Competence of Russian Language and Literature Teachers (Journal of Educational Sciences, 2019)
The article is devoted to the actual problem of the formation of professional communication competence of a teacher. The potential of electronic educational resources and the practical use of the techniques and skills of activities in the information educational environment in the context of future professional activity are considered. The use of electronic educational resources makes it possible to provide a highly informative capacity of educational and linguistic material and contributes to the creation of optimal conditions for the training of future teachers of Russian and literature. Digital pedagogy approaches information technologies as an integral part of educational and methodologicalcomplexes, considering them as factors that contribute to the formation of professional competence of future teachers in Russian language and literature. The new teaching method developed was tested at Al-Farabi Kazakh National University. At the initial stage, students’ preferences were studied. A survey of 350 students of pedagogical specialization was done. The questionnaire included two sets of questions: on the positivity / negativity of the acceptance of the new methodology and the means of instruction; evaluation of the usefulness and informational saturation of the training tool. Overall, 69% of students liked the developed method; as noted by the respondents, the information educational environment improves the learning process (84%); facilitates the assimilation of educational material (80%), and allows you to independently study the educational material (71%).Key words: information and educational environment, communication competence, electronic educational resources, interactive learning tasks, professional activities.